2011
DOI: 10.1073/pnas.1103869108
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with HIV Gag targeted to dendritic cells followed by recombinant New York vaccinia virus induces robust T-cell immunity in nonhuman primates

Abstract: Protein vaccines, if rendered immunogenic, would facilitate vaccine development against HIV and other pathogens. We compared in nonhuman primates (NHPs) immune responses to HIV Gag p24 within 3G9 antibody to DEC205 (“DEC-HIV Gag p24”), an uptake receptor on dendritic cells, to nontargeted protein, with or without poly ICLC, a synthetic double stranded RNA, as adjuvant. Priming s.c. with 60 μg of both HIV Gag p24 vaccines elicited potent CD4 + T cells secreting IL-2, IFN-γ, and TNF-α, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 44 publications
8
109
0
2
Order By: Relevance
“…In the present study, we have solely relied on the use of OVA as a source of Ag for presentation. Ags other than OVA are presented following receptor targeting including HIV Gag (8,42,43) and human epidermal growth factor receptor 2 (44,45), highlighting the usefulness of Ab-targeted vaccination in settings of infection and cancer immunotherapy, respectively. We propose that findings identified in the present study are relevant to any Ag that is internalized via a specific receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have solely relied on the use of OVA as a source of Ag for presentation. Ags other than OVA are presented following receptor targeting including HIV Gag (8,42,43) and human epidermal growth factor receptor 2 (44,45), highlighting the usefulness of Ab-targeted vaccination in settings of infection and cancer immunotherapy, respectively. We propose that findings identified in the present study are relevant to any Ag that is internalized via a specific receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Nonhuman primates, and particularly macaques, are privileged animal models for such preclinical vaccinal studies. Although CD205 targeting has been shown to be immunogenic in macaques (22), studies in humans have demonstrated that CD205 is quite promiscuously expressed in primates (23 , and human CD141 + mDC should express the same conserved membrane markers, share the same transcriptomic signature, and be highly reactive to TLR3 triggering. Indeed, we were able to: 1) identify lineage (lin) neg XCR1 + mDC in rhesus macaques using polychromatic flow cytometric labeling with Abs and fluorochrome-labeled XCL1; 2) confirm by real-time PCR the expression pattern of all of the genes tested as compared with other macaque myeloid cells; and 3) demonstrate their unique high reactivity to TLR3 triggering for TNF-a production and CD40 upregulation.…”
Section: Ouse Cd8amentioning
confidence: 99%
“…Compared to the mouse homolog, hDEC-205 protein exhibits ~80% identity, suggesting functional properties that are conserved between species. In fact, humanized recombinant anti-hDEC-205 mAbs fused to HIV-derived Gag peptides efficiently target DCs and elicit strong CD4 + and CD8 + T cell responses in vivo, both in mice with CD11c promoter-driven transgenic expression of hDEC-205 [56] and in rhesus macaques [57]. Finally, it appears worthwhile mentioning that a fully human anti-hDEC-205 mAb linked to NY-ESO-1 is currently in phase 1-2 development (Celldex Therapeutics, USA) for the treatment of a variety of cancers that express the tumor Ag NY-ESO-1.…”
Section: Dec-205 + DC Targeting To Enhance Ag-specific T Cell Immunitymentioning
confidence: 99%